Proteomics in kidney disease: clinical considerations - Rossing, Peter (Henry Stewart Talks, 2013)
Proteomics for clinical use, Available and applied single risk marker strategies in nephrology based on hypothesis driven biomarker search, Open or unbiased multimarker approaches including plasma and urine proteomics, Examples from different renal diseases, Data from cross sectional and longitudinal studies, Proteomics may provide insight into disease pathology, Proteomics may provide risk stratification for clinical trials, Example: intervention trial for type 2 diabetic subjects with high risk urinary proteomic pattern
Archived at 2023/03/30